A gazdasági fejlettség tényezőinek regionális különbségei az Európai Unióban - Szabó, Pál (Jelenkori Társadalmi és Gazdasági Folyamatok, 2009)
This paper focuses on the structure of economic development (in connection with la-bour productivity and employment) of the EU regions. The classical disintegration of the statistical data of development is: GDP/population=GDP/employment*employment/population. We compare the régional (NUTS 2) disparities of these factors in the EU based on the given statistical data (source: Eurostat) and we analyse the relationship between them. We pay special attention to the situation of the Hungárián regions.